Answer:
0.44444444 or 4/9
Step-by-step explanation:
Since we know the value of
, we can rewrite the equation replacing the variables.
![\frac{2}{3}^{2} + 3*\frac{2}{3} - 2](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%5E%7B2%7D%20%2B%203%2A%5Cfrac%7B2%7D%7B3%7D%20-%202)
Now solve. While solving, remember the order of operations.
or ![\frac{4}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B9%7D)
So we just do
cost/number of people=cost per 1 person
so
(6p)/(3p^2)
remember that you can split it up and make ones
![\frac{6p}{3p^{2}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6p%7D%7B3p%5E%7B2%7D%7D%20)
=
![\frac{6}{3p}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B3p%7D%20)
times
![\frac{p}{p}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bp%7D%7Bp%7D%20)
=
![\frac{2}{1p}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B1p%7D%20)
times
![\frac{p}{p}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bp%7D%7Bp%7D%20)
times
![\frac{3}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B3%7D%20)
=
![\frac{2}{1p}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B1p%7D%20)
times 1 times 1=2/p
easy way is
remember that
(x^m)/(x^n)=x^(m-n)
so
(6p)(3p^2)=6/(3p=2/p=2p^-1
each member pays 2/p
Answer:
x = -96
Step-by-step explanation:
Question
10 to the second power+6.7+8
Answer:
<h2>
114.7</h2>
Step-by-step explanation:
10² + 6.7 + 8 =
100 + 6.7 + 8 =
114.7
Answer:
x = -1
x = 5
Step-by-step explanation:
Use pythagorean theorem: a² + b² = c²
x² + (2x + 2)² = (2x + 3)²
Since these are quantities, you'll have to make them into quadratic equations.
(2x + 2)(2x + 2) = 4x² + 4x + 4x + 4
(2x + 3)(2x + 3) = 4x² + 6x + 6x + 9
x² + 4x² + 4x + 4x + 4 = 4x² + 6x + 6x + 9
Combine like terms
5x² + 8x + 4 = 4x² + 12x + 9
Move one side to set the equation equal to 0
x² - 4x - 5 = 0
Solve
x² - 5x + x - 5 = 0
x(x - 5) + 1(x - 5) = 0
(x + 1)(x - 5) = 0
x = -1, 5
<em>We</em><em> </em><em>can</em><em> </em><em>check</em><em> </em><em>that</em><em> </em><em>these</em><em> </em><em>are</em><em> </em><em>correct</em><em> </em><em>by</em><em> </em><em>plugging</em><em> </em><em>them</em><em> </em><em>in</em><em> </em><em>for</em><em> </em><em>x</em><em> </em><em>and</em><em> </em><em>seeing</em><em> </em><em>if</em><em> </em><em>they</em><em> </em><em>are</em><em> </em><em>equal</em>
<em>For</em><em> </em><em>example</em>
<em>(</em><em>-1</em><em>)</em><em>²</em><em> </em><em>+</em><em> </em><em>(</em><em>2</em><em>(</em><em>-1</em><em>)</em><em> </em><em>+</em><em> </em><em>2</em><em>)</em><em>²</em><em> </em><em>=</em><em> </em><em>(</em><em>2</em><em>(</em><em>-1</em><em>)</em><em> </em><em>+</em><em> </em><em>3</em><em>)</em><em>²</em>
<em>1</em><em> </em><em>=</em><em> </em><em>1</em>